139k views
5 votes
Using the quadratic formula, solve:3p^2 - p - 3 = 0

User Mulhoon
by
5.7k points

1 Answer

6 votes

Answer:

x = 1.18 or x = -0.85

Step-by-step explanation:

Given the equation:


3p^2-p-3=0

Solving using the quadratic formula:


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

Here, a = 3, b = -1, c = -3


\begin{gathered} x=\frac{-(-1)\pm\sqrt[]{(-1)^2-4(3)(-3)}}{2(3)} \\ \\ =\frac{1\pm\sqrt[]{1+36}}{6} \\ \\ =\frac{1\pm\sqrt[]{37}}{6} \end{gathered}

Therefore,


\begin{gathered} x=\frac{1+\sqrt[]{37}}{6} \\ \\ =1.18 \end{gathered}

OR


\begin{gathered} x=\frac{1-\sqrt[]{37}}{6} \\ \\ =-0.85 \end{gathered}

User Idobr
by
5.6k points